(untitled) (International Journal of Engineering and Computer Science, 2025)
With the growing need to create highly efficient and interactive web applications, WebSockets technology is becoming increasingly important due to its ability to provide instant and two-way communication between the client and the server. This article explores the impact of WebSockets on the performance of web applications and demonstrates how this technology can be a solution for tasks where traditional interaction methods such as Ajax and short polls are insufficient. Particular attention is paid to applications that require high performance and minimal data latency, including online games, chat rooms, and real-time monitoring systems. The article discusses the problems of increased server load and data exchange delays typical of traditional methods, and provides examples of successful WebSockets implementation, which significantly optimizes application performance, minimizing response time and improving overall user-system interaction.